Navoi's "Tomadur" Ghazal Performance (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
In this article, the work of the great poet Alisher Navoi, who came to the attention of the great historian Ali Yazdi, appreciated the talent of Maulana Lutfi, won the recognition of Kamal Turbati, studied under teachers such as Sayyid Hasan Ardasher, Pahlavon Muhammad, collaborated with Abdurahman Jami, in particular, his "Tomadur" It talks about the ghazali festival and the art forms skillfully used in it.